PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KEPUASAN KERJA PEGAWAI PADA KANTOR SATUAN POLISI PAMONG PRAJA KOTA BIMA - Agus Gunawan; Firman Kusmayadin (Universitas Sarjanawiyata Tamansiswa, 2021)
This study aims to determine whether the transformational leadership style has a significant effect on employee job satisfaction at the Civil Service Police Unit Office of Bima City. With the sampling technique using purposive sampling. The population used in this study were 228 employees with details of 82 civil servants and 146 contract workers. The sample used in this study amounted to 82 civil servants. The research method used simple linear regression to obtain a good regression value, first tested the validity and reliability test. And the results of this study indicate that the leadership style of the transformation has no effect on the performance of employees at the Civil Service Police Unit Office of Bima City. Based on statistical calculations, Thus it was decided that the hypothesis that says there is a significant influence between transformation leadership style on employee performance at the civil service police unit office in Bima City with Ha rejected and Ho is accepted, which means that the leadership style of the transformation (X), has no significant effect on employee performance (Y).